Images and Words The Voice of Pramoedya Ananta Toer in Contemporary Art - Karja, I Wayan (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
Pramoedya Ananta Toer’s literary works expose histories of oppression, resistance, and national identity, giving voice to those silenced by colonialism and authoritarianism. While his influence on literature is widely acknowledged, its intersection with contemporary visual art remains underexplored. This article examines how text-based artistic practices reinterpret and extend Pramoedya’s legacy, using layering, erasure, and fragmentation as visual metaphors for censorship and resilience. Drawing on cognitive theory, expression theory, and visual semiotics, the artistic process integrates his words into images of painting and mixed media to create a dialogue between past and present, literature and image, memory and erasure. The findings reveal that visualizing literary narratives deepens historical reflection and challenges cultural amnesia. This study contributes to both artistic and academic discourse by showing how contemporary art can reclaim silenced histories and expand Pramoedya’s influence beyond literature into the realm of visual expression.